Detection of an IL-6 Biomarker Using a GFET Platform Developed with a Facile Organic Solvent-Free Aptamer Immobilization Approach - Khan, Niazul I. (Sensors (Basel), 2021)
Aptamer-immobilized graphene field-effect transistors (GFETs) have become a well-known detection platform in the field of biosensing with various biomarkers such as proteins, bacteria, virus, as well as chemicals. A conventional aptamer immobilization technique on graphene involves a two-step crosslinking process. In the first step, a pyrene derivative is anchored onto the surface of graphene and, in the second step, an amine-terminated aptamer is crosslinked to the pyrene backbone with EDC/NHS (1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride/N-hydroxysuccinimide) chemistry. However, this process often requires the use of organic solvents such as dimethyl formamide (DMF) or dimethyl sulfoxide (DMSO) which are typically polar aprotic solvents and hence dissolves both polar and nonpolar compounds. The use of such solvents can be especially problematic in the fabrication of lab-on-a-chip or point-of-care diagnostic platforms as they can attack vulnerable materials such as polymers, passivation layers and microfluidic tubing leading to device damage and fluid leakage. To remedy such challenges, in this work, we demonstrate the use of pyrene-tagged DNA aptamers (PTDA) for performing a one-step aptamer immobilization technique to implement a GFET-based biosensor for the detection of Interleukin-6 (IL-6) protein biomarker. In this approach, the aptamer terminal is pre-tagged with a pyrene group which becomes soluble in aqueous solution. This obviates the need for using organic solvents, thereby enhancing the device integrity. In addition, an external electric field is applied during the functionalization step to increase the efficiency of aptamer immobilization and hence improved coverage and density. The results from this work could potentially open up new avenues for the use of GFET-based BioMEMS platforms by broadening the choice of materials used for device fabrication and integration.